Four Methods of Recruiting Couples Into a Longitudinal Study of Physical Activity in People With Osteoarthritis: Recruitment, Retention, and Lessons Learned - Carthron, Dana L.; Phillips, Ashley; Cuthbertson, Carmen C.; Ellis, Katrina R.; Altpeter, Mary; Callahan, Leigh F.; Bahorski, Stephanie; Rini, Christine (Frontiers in Public Health, 2018)
Increases in physical activity can reduce joint pain among people with osteoarthritis (PWOA) who are insufficiently physically active. Because evidence suggests that social support from intimate partners may help PWOA become more active, researchers have been interested in recruiting couples to studies of physical activity interventions; however, little guidance exists describing efficient and effective strategies for engaging couples in research. We describe methods used to recruit couples and contrast methods in terms of the proportion of individuals enrolled, sample demographic composition, retention, and resources. We used four recruitment methods to enroll couples in a longitudinal study of PWOA: (1) visiting community sites, (2) sending university-wide emails, (3) contacting patients identified through electronic medical records (EMR), and (4) partnering with a county-based osteoarthritis (OA) research cohort. We found that these methods differed in their challenges and contribution to enrollment goals but demonstrated similar levels of retention. We contacted 747 PWOA; 56% were screened for eligibility and 23% enrolled in the study. The largest proportion of participants recruited were from the email method (35.1%), followed by the community (26%), EMR (22.0%), and OA cohort (19.6%). Couples enrolled through the different methods differed by age, employment, education, and household income. Across the methods for both PWOA and partners, over 80% of participants were non-Hispanic white, about 11% were non-Hispanic black, and 6–8% identified as another race. Over 12 months of follow-up, 31 (17.9%) PWOA and 36 (20.8%) partners were lost to follow-up. Using four distinct recruitment methods allowed us to meet recruitment goals and provided a broader, more diverse population compared to using one method. We recommend that researchers consider several recruitment methods to meet enrollment goals, to ensure a diverse sample, and to match available resources. The lessons learned from this research fill a critical gap in the understanding of how to overcome barriers to recruiting and retaining couples in behavioral research.